TREINAMENTO DE FORÇA DURANTE A ADOLESCÊNCIA REPROGRAMA AS ALTERAÇÕES METABÓLICAS EM PROLE DE RATAS EXPOSTAS NA GESTAÇÃO E LACTAÇÃO A UMA DIETA RICA EM SACAROSE - RIBEIRO, Nathalee Liberal Xavier (2023)
Metabolic syndrome, also known as syndrome X, is a pathological condition defined by the World Health Organization (WHO) characterized by the presence of abdominal obesity, insulin resistance, hypertension, and hyperlipidemia. The increasing prevalence of metabolic disturbances is linked to genetic factors, physical inactivity, and the rising consumption of hypercaloric foods, particularly those containing added sugars such as sucrose and fructose, commonly found in processed foods and sodas. Maternal intake of sucrose before and during pregnancy, as well as during lactation, has detrimental effects on the metabolism of their offspring, although these effects can be attenuated by moderate to intense strength training. This study investigated the impact of resistance training on the offspring of rats exposed to a sucrose-rich diet during pregnancy and lactation, as well as its implications on metabolic programming. The results revealed that a sucrose-rich diet for mothers caused metabolic dysfunctions in their male offspring, and exercise during adolescence was insufficient to reverse these metabolic changes. Collectively, these findings suggest that the impaired metabolic environment of DRSF0 rats had a negative impact on the morphofunctional profile of DRSF1 offspring, leading to changes consistent with metabolic syndrome and an increase in (peri)gonadal organs and tissue mass, which may be associated with reproductive dysfunctions in these animals. Furthermore, the consistent reduction in inter-scapular adipose tissue mass, with consequent decreased heat production, may be related to overall adiposity increase at ages beyond those analyzed in this study. Remarkably, DRS-TF1 offspring, consisting of the sons of DRSF0 rats who underwent strength exercises during adolescence, exhibited reduced body weight at the end of the training period at 51 days of age when compared to the DRSF1 group that did not undergo training. Regarding metabolic impacts, strength training during adolescence proved effective in reprogramming glucose homeostasis in the DRS-TF1 group. In this context, it is essential to recognize the importance of strength training in adolescence as a potentially effective strategy to mitigate the adverse effects of a harmful metabolic environment, offering promising prospects for the prevention and treatment of metabolic disorders in youth.